ChemInform Abstract: Switching the Structure Type upon Ag Substitution: Synthesis and Crystal as well as Electronic Structures of Li12AgGe4. Issue 14 (March 2016) - Henze, Alexander; Faessler, Thomas F.
Abstract: In view of its potential use as anode material in Li ion batteries, Li12 AgGe4 is discovered as the Li‐richest phase in the ternary phase system.